Peran Lingkungan Pendidikan Islam dalam Mewujudkan Keteladanan Sosial - Asman, Nurfani Maulidina; Agustin, Amelia; G, Gusmaneli (Socius: Jurnal Penelitian Ilmu-Ilmu Sosial, 2025)
Islamic educational environments namely family, school, and community play an important role in shaping exemplary behavior in students. This article discusses how Islamic values can be instilled through these environments to build good social character. Using a descriptive approach, the article highlights the importance of role modeling in education, and the need for collaboration among parents, teachers, and society. The findings show that when the educational environment aligns with Islamic teachings, students are more likely to adopt positive attitudes and become individuals who contribute to their surroundings.